(untitled) (Swiss Medical Weekly, 2017)
BACKGROUND Population based studies show a steady increase in adult patients with congenital heart defects. The aim of this study was to assess the evolution of such a patient cohort and its burden on clinical care at a dedicated tertiary care centre. METHODS All patients with congenital heart disease followed up by a dedicated multidisciplinary team at our institution were identified (n = 1725). Disease characteristics, the increase in patient numbers and interventions and the increase in selected complications were analysed and compared between the first (1996–2005) and second (2006–2015) decades of the study period. RESULTS Between the two decades of the study period, the number of patients in follow-up increased by 109%, the number of patients who died or underwent transplantation more than doubled and the number of outpatient visits increased by 195%. One fourth of all patients underwent at least one surgical procedure and 14% had at least one percutaneous intervention. The increase in surgical procedures between the two decades was 27% and the increase in percutaneous interventions 159%. Between the two decades the number of patients requiring direct current cardioversion increased from 32 to 95 (+197%), the number of patients requiring admission for infective endocarditis increased from 7 to 29 (+314%) and the number of women followed up during pregnancy increased from 18 to 115 (+539%). CONCLUSION As a result of the increasing number and complexity of adult survivors with congenital heart disease more resources will be needed to cope with the demands of this novel cohort of complex patients in adult cardiology.